Antiviral Activity of Some Indian Medicinal Herbs - P, Kalyani; Z, Kamaruz (Indian Journal of Pharmacy Practice)
Viral diseases, including emerging and chronic viruses, are an increasing worldwide health concern. As a consequence, the discovery of new antiviral agents from plants has assumed more urgency than in the past. A number of native Indian medicines of plant origin are known to have antimicrobial and anti-inflammatory activity, although only a few have been studied for their antiviral properties and immunomodulating effects.The number of patients seeking alternate and herbal therapy is growing exponentially. Herbal medicines are the synthesis of therapeutic experiences of generations of practicing physicians of indigenous systems of medicine for over hundreds of years. Herbal medicines are now in great demand in the developing world for primary health care not because they are inexpensive but also for better cultural acceptability, better compatibility with the human body and minimal side effects.This review gives an overview of some important medicinal plants with antiviral activity which are traditionally used in India.
Keywords: Antiviral; Herbal medicine; immunomodulating effects